Sfera wolności. Zygmunta Mycielskiego uwagi o muzyce 1955 - HENDRYKOWSKI, MAREK (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2016)
The sphere of freedom. Zygmunt Mycielski observations on music in 1955 The article profiles one of the most interesting music critics of the communist period. Zygmunt My- cielskis journalism is one of the most valuable phenomena of Polish postwar musical culture. What was important for him were fixed points, imponderables keeping human thinking in check and truly creative activity in the sphere of sound. He did not share Carl Dahlhaus’ idea of the death of aesthetics, which was fashionable in the early twentieth century He was convinced that the aesthetic value of a musical work shape musical and non-musical reality, and that the microenvironment which these values form and unify remains particularly important for a man enslaved by the totalitarian system.